The idea of Mankind in the declarations of human rights - Mac Gregor, Felipe E. (1993)
The article maintains that all human beings possess a vision of mankind based on a vast number of personal experiences. However, in spite of the fact that this infinite number of experiences can result in a parallel number of views, all these individual outlooks on mankind share a common nucleus, one that gives rise to the universal declarations on human rights.